Evolution and variations of atmospheric VOCs and O3 photochemistry during a summer O3 event in a county-level city, Southern China. (1st March 2022) - Liu, Yafei; Qiu, Peipei; Li, Chenlu; Li, Xueke; Ma, Wei; Yin, Shijie; Yu, Qing; Li, Jifeng; Liu, Xingang
Abstract: Studies on ambient volatile organic compound (VOC) and ozone (O3 ) pollution in county-level cities in China are scarce. The variations of atmospheric VOCs and O3 photochemistry on O3 pollution and non-O3 pollution period were explored in summer 2019 in a typical county-level city, Southern China. The average O3 concentration was 84.2 ppbv during an O3 episode, which was more than 1.6 times higher than that on non-O3 pollution days. The VOC concentration was 20.0 ± 4.5 ppbv during the sampling period, which was about × 1.5 lower than megacities and suburban areas. The OH, HO2, and RO2 radicals and O3 photochemistry are simulated using a box model. O3 formation was dominated by the reaction of HO2 +NO. OH + NO2 was the major contributor to O3 destruction. The net O3 production rates were higher on O3 episode days as compared to non-O3 episode periods. O3 formation regimes were explored using the empirical kinetics modelling approach (EKMA). The shift of wind directions led to the change from transition regimes to NOX -limited regimes. Industrial source was a critical element in the increasing VOC concentrations, compositions, the transition of O3 formation regimes, and formation of O3 episodes. The results revealed that O3 formation in the Yangxin County was governed by interplay of meteorological conditions, O3 precursors, emissions sources, air mass transport, photochemical production conditions, and O3 formation regimes. There were distinct chemical features in the atmosphere of county-level cities and megacities. Graphical abstract: Image 1 Highlights: County-level cities and megacities had distinct chemical features in atmosphere. O3 formation regimes shifted with wind directions. Industrial plumes rather vehicles contributed greatly to the ambient VOCs. More efficient radical cycling and rapid O3 accumulation on O3 pollution days. Local photochemistry and import greatly impacted on daytime O3 formation.